ESTETIKA, RETORIKA, DAN IDEOLOGI PENGARANG DALAM NOVEL NIJUUSHI NO HITOMI (DUA BELAS PASANG MATA) KARYA SAKAI TSUBOI (KAJIAN STILISTIKA) - andari, Novi; Bahalwan, Khaira Imandiena (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
Sakai Tsuboi was one the Japanese writers who won rewards. One of his works Nijuushi no Hitomi won a lot of appreciation from its readers. In this novel, Tsuboi showed his ideology of passivism or the love for peace and anti-war. The language of Nijuushi no Hitomi succeeded in attracting readers’ attention, emotion, and thoughts. There were relationships among the dictions, language style, rethorics, and these relationships did not reduce the writer’s esthetical sense toward the sociohistorical events. Keywords : Estetika, Retorika, Ideologi Pengarang, Gaya Bahasa